1987
DOI: 10.1111/j.1464-410x.1987.tb09124.x
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy and Limitations of Ultrasound in the Assessment of Venous Extension in Renal Carcinoma

Abstract: Ultrasound was used to assess venous extension in 28 patients with renal carcinoma, with particular reference to involvement of the inferior vena cava. The findings were correlated with surgical findings in all except two patients who had gross caval involvement and metastatic disease and in whom surgery was considered inappropriate. In 10 of the 28 patients (36%), a diagnostic ultrasound examination of the cava from the renal veins to the diaphragm was obtained. In four of these, ultrasound showed tumour invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The second hypothesis is related to the adipose tissue thickness that may cause technical difficulties for the performance of this exam. The thick layers of subcutaneous fat in obese people may mislead the examiner's judgment of liver echogenicity, as cited in visualizing of the abdominal aorta [12] and renal carcinoma [13] . The image quality rate also has been discussed and different results have as been found.…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis is related to the adipose tissue thickness that may cause technical difficulties for the performance of this exam. The thick layers of subcutaneous fat in obese people may mislead the examiner's judgment of liver echogenicity, as cited in visualizing of the abdominal aorta [12] and renal carcinoma [13] . The image quality rate also has been discussed and different results have as been found.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the visualisation of the renal veins and vena cava was inadequate in 54% and 2 1 % of patients respectively. The corresponding figures from Webb et al (1987) are 75% and 64% and from Schwerk etal. 1985) 34.2% and 4.2%.…”
Section: Resultsmentioning
confidence: 83%
“…Vena caval extension should be excluded in all patients with renal carcinoma, since less than half have clinical signs of vena caval obstruction. Ultrasound is an accurate diagnostic technique in these circumstances (Webb et al, 1987) and is the investigation of choice because it is painless, readily available and non-invasive. In this study of 13 patients it yielded only 1 false negative result and even this was recognised as equivocal.…”
Section: Discussionmentioning
confidence: 99%